Evaluating mental workload in manufacturing: A decision support perspective on production line operators - Hadyanawati, Anindya Agripina (Jurnal Mantik, 2025)
Mental workload is the gap between the requirements of a task and a person's highest achievable capacity when working under motivated conditions. At PT. XYZ, the high production demands have resulted in significant overtime hours for employees. In one of the production buildings, employees are reported to work overtime almost daily. According to overtime records, individual employees experience up to 143 hours of overtime per month. This study investigates the mental workload of production line employees using the NASA-TLX questionnaire, followed by a cause-and-effect analysis. The NASA-TLX assessment classified all operators as experiencing high levels of mental workload. These findings were further analyzed through a cause-and-effect diagram, which revealed that high mental workload levels were influenced by human factors, equipment, methods, and the working environment.